Investigación sobre patologias de labio y/o paladar hendidos en pacientes de la Clínica Noel de Medellín: estudio piloto (reporte de investigación) - Giraldo-Fernández, Mónica Patricia; Mesa-Montoya, Angela María (Revista Facultad de Odontología Universidad de Antioquia, 2016)
This investigation is an epidemiological retrospective and descriptive study. It was realized in patients with deft lip and/or cleft palate of NoelClrnicinMedelhn. 379 clinical files were revised .from patients that were treated with surgery to correct lip and/or palate during 1984 and 1987 years with the purpose to detect risk factors associated with this anomaly. The cleft- more frec-uerztly showed was bilateral queilopalatosquisis horn primary and secundazy palate and then left side. The lip and palate fisures with exception palatosquisis and b ifid uvula, were morthecuently in men that women in all cases. There was not associatdon between presence of deft and parent’s advanced age. Several pathologies and drugs ingestion durirzg pregnancy and familiar antecedents were not anlized because files data were insufficient.